ANALISIS RASIO KEMANDIRIAN KEUANGAN DESA DAN RASIO PERTUMBUHAN DESA TERHADAP KINERJA KEUANGAN DESA TAHUN 2014 – 2015 (Studi Kasus di desa Kecamatan Sumberlawang dan Kecamatan Miri) - Fitri Aisah, Suhendro & Riana Dewi (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this research was to analyze the financial performance of thevillage in the village and Sub district Sumberlawang and Subdistrict Miri, Sragendistrict 2014 – 2015. This research is descriptive research using this type ofqualitative approach. Data collected with the documentation. Data analysis usingratio analysis financial independence the village and village growth ratio. Theresults showed the financial performance of the village in the village in district andsub district Sumberlawang Miri by 2014 to 2015 indicate the level of financialindependence the village was still low with an average level of financialindependence village in sub district of Sumberlawang of 12.5% by 2014 and 201510,3% and 19,9% of Miri subdistrict 2014 and 9,9% in 2015, the growth rate of thevillage in the sub district of Sumberlawang for the original village of income andtotal revenue has decreased growth, shopping routine and development spending hasincreased growth and the growth rate of the village in district of Miri for totalrevenues, shopping routine and development spending has increased fluctuatinggrowth. This indicates that financial performance is still low and not optimal so thatneeds to be improved again its main sectors of the original village of income.Keywords: financial self-sufficiency ratio ratio of the growth of the village, thevillage, the village's financial performance